Intron loss and gain during evolution of the catalase gene family in angiosperms. - Frugoli, J A (1998)
Angiosperms (flowering plants), including both monocots and dicots, contain small catalase gene families. In the dicot, Arabidopsis thaliana, two catalase (CAT) genes, CAT1 and CAT3, are tightly linked on chromosome 1 and a third, CAT2, which is more similar to CAT1 than to CAT3, is unlinked on chromosome 4. Comparison of positions and numbers of introns among 13 angiosperm catalase genomic sequences indicates that intron positions are conserved, and suggests that an ancestral catalase gene common to monocots and dicots contained seven introns. Arabidopsis CAT2 has seven introns; both CAT1 and CAT3 have six introns in positions conserved with CAT2, but each has lost a different intron. We suggest the following sequence of events during the evolution of the Arabidopsis catalase gene family. An initial duplication of an ancestral catalase gene gave rise to CAT3 and CAT1. CAT1 then served as the template for a second duplication, yielding CAT2. Intron losses from CAT1 and CAT3 followed these duplications. One subclade of monocot catalases has lost all but the 5'-most and 3'-most introns, which is consistent with a mechanism of intron loss by replacement of an ancestral intron-containing gene with a reverse-transcribed DNA copy of a fully spliced mRNA. Following this event of concerted intron loss, the Oryza sativa (rice, a monocot) CAT1 lineage acquired an intron in a novel position, consistent with a mechanism of intron gain at proto-splice sites.